C / N-NiCoMn-LDH / Ag composite electrode material and preparation method thereof

By preparing C/N-NiCoMn-LDH/Ag composite electrode material with a hollow cage structure with a nanosheet assembly and a low crystallinity, the problems of low specific capacitance and poor cycle stability of nickel-cobalt-based electrode material are solved, and high specific capacitance and excellent cycle stability are achieved, and it is suitable for high-performance supercapacitors.

CN115148972BActive Publication Date: 2025-03-18NORTHEAST DIANLI UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210839456.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-18
Publication Date
2025-03-18
Estimated Expiration
2042-07-18

AI Technical Summary

Technical Problem

Nickel-cobalt-based transition metal compounds, as supercapacitor electrode materials, have problems such as lower actual capacitance and poor cycle stability, and it is difficult to meet the requirements of high-performance supercapacitors.

Method used

By designing a reasonable material preparation process, a hollow cage-like structure with a unique nanosheet assembly and a low crystallinity C/N-NiCoMn-LDH/Ag composite electrode material is prepared, and the electrochemical reaction activity and charge storage ability of the material are improved by regulating multiple compositions, microstructures and crystal structures.

Benefits of technology

It significantly improves the electrochemical performance of the material, improves the specific capacitance and cycling stability, and improves the adsorption capacity of electrolyte ions, and is suitable for high-performance supercapacitor applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115148972B_ABST
    Figure CN115148972B_ABST
Patent Text Reader

Abstract

The present invention discloses a C / N‑NiCoMn‑LDH / Ag composite electrode material and a preparation method thereof, which are characterized in that the material comprises the preparation of a ZIF‑67 precursor and the preparation of a C / N‑NiCoMn‑LDH / Ag composite electrode material, and the crystallinity and surface active sites thereof are effectively regulated by introducing Mn and Ag elements, and the relatively low crystallinity of the material makes it have a high electrochemical reaction activity, and at the same time, the material is novel in that the sheet assembles a hollow cage structure, the multi-metal composition characteristics and the double-layer protection of nitrogen heteroatom-doped carbon are utilized to improve the electrochemical performance of the material. The method is scientific and reasonable, simple and controllable, and has strong applicability, and can efficiently prepare a composite electrode material with excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials and relates to the preparation of electrode materials for supercapacitors, and specifically, is a C / N-NiCoMn-LDH / Ag composite electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of electronic devices and hybrid vehicles, technicians in this field are committed to developing electrochemical energy storage devices with high stability and high output power characteristics. Compared with traditional energy storage devices, supercapacitors are favored due to their good cycle stability and high power density. However, their relatively low energy density greatly limits their practical application in various electronic devices. According to the energy density calculation formula, E = 1 / 2CV 2 , the energy density of energy storage devices can be improved by increasing the specific capacitance (C) and the operating voltage (V). Therefore, the design and development of supercapacitor electrode materials with high specific capacitance has become an effective way to improve the electrochemical energy storage performance of energy storage devices. Nickel-cobalt-based transition metal compounds are ideal electrode materials for supercapacitors due to their high theoretical specific capacitance and rich valence states, but they still have shortcomings such as low actual specific capacitance and poor cycle stability. H Kuang et al. used a simple microwave method to compound the petal-shaped NiCo-LDH and the three-dimensional GNSs skeleton to prepare NiCo-LDH@GNSs nanocomposite materials. The electrochemical test results show that at 1A·g -1 At this current density, the specific capacitance of the composite material is 1470F·g -1 ; After 1000 charge and discharge cycles, its specific capacitance retention rate is 81.6%. Although the specific capacitance of the nickel-cobalt-based composite electrode material prepared in this study has been improved to a certain extent, it is still difficult to meet the requirements of high-performance supercapacitors, and its cycle stability needs to be further improved. (H Kuang, H Zhang, X Liu, et al. Microwave assisted synthesis of NiCo-LDH / graphene nanoscrolls composite for supercapacitor, Carbon. 2022, 190, 57-67.).

[0003] From the above analysis, it can be seen that nickel-cobalt-based compounds have great application prospects as supercapacitor electrode materials, but there is a large gap between their actual specific capacitance and theoretical specific capacitance, and their cycle stability needs to be further improved. The present invention prepares a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled with unique nanosheets and low crystallinity by rationally designing the material preparation process. Based on the multi-component composition, microstructure and crystal structure regulation of the material, the electrochemical reaction activity and charge storage capacity of the material are significantly improved. Summary of the invention

[0004] The purpose of the present invention is to propose a method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material with excellent electrochemical performance, multi-component composition, and adjustable microstructure and crystal structure in order to solve the technical problems that technicians in the field are eager to solve but have not yet solved, and to provide a C / N-NiCoMn-LDH / Ag composite electrode material obtained by the method.

[0005] One of the technical solutions adopted to achieve the purpose of the present invention is: a method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material, characterized in that it comprises the following steps:

[0006] 1) Preparation of ZIF-67 precursor

[0007] (1) preparing 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution respectively, then mixing the two solutions in equal volumes, stirring for 1 to 30 minutes, and aging the mixed solution at room temperature for 20 to 28 hours;

[0008] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0009] (3) placing the product washed in step (2) of step 1) in a forced air drying oven and drying at 50° C. to constant weight to obtain a ZIF-67 precursor;

[0010] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0011] (1) Take 1 portion of the ZIF-67 precursor obtained in step 1) and ultrasonically disperse it in a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution is a mixture of anhydrous ethanol and ultrapure water, and the volume ratio of anhydrous ethanol to ultrapure water is 1:9-49. The concentration of the obtained ZIF-67 dispersion is 0.5 g / L-1 g / L, and then 1 / 4-2 portions of dopamine hydrochloride (C8H 12ClNO2), magnetically stir for 0.5h, then add 1 / 8 to 1 part of manganese acetate (C4H6MnO4·H2O) and 1 / 10 to 3 / 10 parts of silver nitrate (AgNO3), and continue stirring at room temperature for 0.5 to 2.5h;

[0012] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0013] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0014] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0015] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 550-700° C. for 1-3 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction is completed;

[0016] (6) taking 1 part of the product obtained in step 2) (5) and ultrasonically dispersing it in a mixed solution of anhydrous ethanol and ultrapure water, wherein the volume ratio of anhydrous ethanol to ultrapure water is 25:1-9, and the obtained dispersion concentration is 0.04 g / L-0.3 g / L, and then adding 4-10 parts of nickel nitrate (Ni(NO3)2·6H2O), continuing ultrasonication for 2 hours, and then reacting in a 110-130°C forced air drying oven for 2-6 hours;

[0017] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0018] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0019] The C / N-NiCoMn-LDH / Ag electrode material is further obtained by using the preparation method of the C / N-NiCoMn-LDH / Ag composite electrode material. The electrode material is a hollow cage structure assembled by nanosheets and a low crystallinity composite electrode material.

[0020] The beneficial effects of the present invention are:

[0021] 1. The C / N-NiCoMn-LDH / Ag composite electrode material proposed in the present invention effectively regulates its crystallinity and surface active sites by introducing Mn and Ag elements. The relatively low crystallinity of the material makes it have high electrochemical reaction activity, but it still has a certain crystal structure, which can ensure its high stability. In addition, by making full use of the synergistic effect of the composite material and the high conductivity of elemental silver, the active sites on the surface of the material can be significantly increased, and its adsorption capacity for electrolyte ions can be improved, thereby improving the electrochemical performance of the material;

[0022] 2. The present invention uses ZIF-67 as a precursor and template, and forms a core-shell structure through the self-polymerization process of dopamine hydrochloride on its surface, and further uses it as an intermediate product to prepare a final product with a novel hollow cage structure, thereby achieving effective regulation of the material microstructure; after calcination, N heteroatom-doped carbon is uniformly loaded inside the material sheet structure and outside the overall hollow structure, forming a double-layer carbon protection, and at the same time, by introducing a positively charged metal source during the self-polymerization process of dopamine hydrochloride, while promoting its polymerization process, multi-metal elements can also be tightly loaded, thereby achieving effective regulation of the material composition, and finally preparing a C / N-NiCoMn-LDH / Ag composite electrode material with a nanosheet-assembled hollow cage structure and low crystallinity. The material preparation method proposed by the present invention is scientific and reasonable, simple and controllable, and has strong applicability, and can efficiently prepare a composite electrode material with excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of C / N-NiCoMn-LDH / Ag prepared in Example 2 of the present invention;

[0024] Figure 2 is a TEM image of C / N-NiCoMn-LDH / Ag prepared in Example 2 of the present invention;

[0025] Figure 3 is the EDS image of C / N-NiCoMn-LDH / Ag prepared in Example 2 of the present invention;

[0026] Figure 4 is the XRD pattern of C / N-NiCoMn-LDH / Ag prepared in Example 2 of the present invention;

[0027] Figure 5 is the XPS graph of C / N-NiCoMn-LDH / Ag prepared in Example 2 of the present invention;

[0028] Figure 6 The C / N-NiCoMn-LDH / Ag electrode material prepared in Example 2 of the present invention has a capacitance of 5 to 50 mV·s -1 Cyclic voltammogram at scan rate;

[0029] Figure 7 The C / N-NiCoMn-LDH / Ag electrode material prepared in Example 2 of the present invention has a 1-20A·g -1 Constant current charge and discharge diagram under current density. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific embodiments.

[0031] Example 1: A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material in Example 1 includes preparing a ZIF-67 precursor and preparing a C / N-NiCoMn-LDH / Ag composite electrode material. The specific steps are as follows:

[0032] 1) Preparation of ZIF-67 precursor

[0033] (1) preparing 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution, taking 25 mL of each, then quickly adding the 2-methylimidazole methanol solution to the cobalt nitrate methanol solution, stirring for 1 min, and aging the mixed solution at room temperature for 20 h;

[0034] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0035] (3) The product washed in step (2) of step 1) is placed in a forced air drying oven and dried at 50° C. to a constant weight to obtain a ZIF-67 precursor.

[0036] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0037] (1) 80 mg of the ZIF-67 precursor obtained in step 1) was ultrasonically dispersed in 80 mL of a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution was a mixture of anhydrous ethanol and ultrapure water, and the volume ratio (V / V) of the two was 1:49. Then, 20 mg of dopamine hydrochloride (C8H 12 ClNO2), magnetically stirred for 0.5 h, then 80 mg of manganese acetate (C4H6MnO4·H2O) and 8 mg of silver nitrate (AgNO3) were added, and stirring was continued at room temperature for 0.5 h;

[0038] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0039] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0040] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0041] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 550° C. for 3 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction;

[0042] (6) 20 mg of the product obtained in step 2) (5) was ultrasonically dispersed in a mixed solution of 52 mL of anhydrous ethanol and ultrapure water, wherein the volume ratio (V / V) of anhydrous ethanol and ultrapure water was 25:1, and then 120 mg of nickel nitrate (Ni(NO3)2·6H2O) was added, and the mixture was ultrasonically dispersed for 2 h and then reacted in a 130°C forced air drying oven for 2 h.

[0043] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0044] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0045] Example 2: A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material in Example 2 includes preparing a ZIF-67 precursor and preparing a C / N-NiCoMn-LDH / Ag composite electrode material. The specific steps are as follows:

[0046] 1) Preparation of ZIF-67 precursor

[0047] (1) Prepare 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution, take 25 mL of each, then quickly add the 2-methylimidazole methanol solution to the cobalt nitrate methanol solution, stir for 5 min, and then age the mixed solution at room temperature for 24 h;

[0048] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0049] (3) The product washed in step (2) of step 1) is placed in a forced air drying oven and dried at 50° C. to a constant weight to obtain a ZIF-67 precursor.

[0050] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0051] (1) 80 mg of the ZIF-67 precursor obtained in step 1) was ultrasonically dispersed in 100 mL of a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution was a mixture of anhydrous ethanol and ultrapure water, and the volume ratio (V / V) of the two was 1:19. Then 40 mg of dopamine hydrochloride (C8H 12 ClNO2), magnetically stirred for 0.5 h, then 24.5 mg manganese acetate (C4H6MnO4·H2O) and 16.9 mg silver nitrate (AgNO3) were added, and stirring was continued at room temperature for 1.5 h;

[0052] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0053] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0054] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0055] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 600° C. for 2 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction;

[0056] (6) 20 mg of the product obtained in step 2) (5) was ultrasonically dispersed in a mixed solution of 60 mL of anhydrous ethanol and ultrapure water, wherein the volume ratio (V / V) of anhydrous ethanol and ultrapure water was 5:1, and then 180 mg of nickel nitrate (Ni(NO3)2·6H2O) was added, and the mixture was ultrasonically dispersed for 2 h and then reacted in a 120°C forced air drying oven for 4 h;

[0057] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0058] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0059] Example 3: A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material in Example 3 includes preparing a ZIF-67 precursor and preparing a C / N-NiCoMn-LDH / Ag composite electrode material. The specific steps are as follows:

[0060] 1) Preparation of ZIF-67 precursor

[0061] (1) Prepare 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution, take 25 mL of each, then quickly add the 2-methylimidazole methanol solution to the cobalt nitrate methanol solution, stir for 15 min, and then age the mixed solution at room temperature for 28 h;

[0062] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0063] (3) The product washed in step (2) of step 1) is placed in a forced air drying oven and dried at 50° C. to a constant weight to obtain a ZIF-67 precursor.

[0064] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0065] (1) 80 mg of the ZIF-67 precursor obtained in step 1) was ultrasonically dispersed in 100 mL of a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution was a mixture of anhydrous ethanol and ultrapure water, and the volume ratio (V / V) of the two was 1:9. Then 80 mg of dopamine hydrochloride (C8H 12 ClNO2), magnetically stirred for 0.5 h, then 10 mg of manganese acetate (C4H6MnO4·H2O) and 24 mg of silver nitrate (AgNO3) were added, and stirring was continued at room temperature for 1 h;

[0066] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0067] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0068] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0069] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 700° C. for 1 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction;

[0070] (6) 20 mg of the product obtained in step 2) (5) was ultrasonically dispersed in a mixed solution of 68 mL of anhydrous ethanol and ultrapure water, wherein the volume ratio (V / V) of anhydrous ethanol and ultrapure water was 25:9, and then 80 mg of nickel nitrate (Ni(NO3)2·6H2O) was added, and the mixture was ultrasonically dispersed for 2 h and then reacted in a 110°C forced air drying oven for 6 h.

[0071] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0072] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0073] Example 4: A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material in Example 4 includes preparing a ZIF-67 precursor and preparing a C / N-NiCoMn-LDH / Ag composite electrode material. The specific steps are as follows:

[0074] 1) Preparation of ZIF-67 precursor

[0075] (1) Prepare 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution, take 25 mL of each, then quickly add the 2-methylimidazole methanol solution to the cobalt nitrate methanol solution, stir for 30 min, and then age the mixed solution at room temperature for 24 h;

[0076] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0077] (3) The product washed in step (2) of step 1) is placed in a forced air drying oven and dried at 50° C. to a constant weight to obtain a ZIF-67 precursor.

[0078] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0079] (1) 80 mg of the ZIF-67 precursor obtained in step 1) was ultrasonically dispersed in 160 mL of a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution was a mixture of anhydrous ethanol and ultrapure water, and the volume ratio (V / V) of the two was 1:19. Then, 160 mg of dopamine hydrochloride (C8H 12 ClNO2), magnetically stirred for 0.5 h, then 24.5 mg manganese acetate (C4H6MnO4·H2O) and 16.9 mg silver nitrate (AgNO3) were added, and stirring was continued at room temperature for 2.5 h;

[0080] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0081] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0082] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0083] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 600° C. for 2 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction;

[0084] (6) 20 mg of the product obtained in step 2) (5) was ultrasonically dispersed in a mixed solution of 64 mL of anhydrous ethanol and ultrapure water, wherein the volume ratio (V / V) of anhydrous ethanol and ultrapure water was 25:7, and then 200 mg of nickel nitrate (Ni(NO3)2·6H2O) was added, and the mixture was ultrasonically dispersed for 2 h and then reacted in a 120°C forced air drying oven for 4 h;

[0085] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0086] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0087] Example 5: A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material in Example 5 includes preparing a ZIF-67 precursor and preparing a C / N-NiCoMn-LDH / Ag composite electrode material. The specific steps are as follows:

[0088] 1) Preparation of ZIF-67 precursor

[0089] (1) Prepare 0.04 mol / L cobalt nitrate (Co(NO3)2·6H2O) and 0.16 mol / L 2-methylimidazole methanol solution, take 25 mL of each, then quickly add the 2-methylimidazole methanol solution to the cobalt nitrate methanol solution, stir for 5 min, and then age the mixed solution at room temperature for 24 h;

[0090] (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times;

[0091] (3) The product washed in step (2) of step 1) is placed in a forced air drying oven and dried at 50° C. to a constant weight to obtain a ZIF-67 precursor.

[0092] 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials

[0093] (1) 80 mg of the ZIF-67 precursor obtained in step 1) was ultrasonically dispersed in 100 mL of a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution was a mixture of anhydrous ethanol and ultrapure water, and the volume ratio (V / V) of the two was 1:19. Then 40 mg of dopamine hydrochloride (C8H 12ClNO2), magnetically stirred for 0.5 h, then 24.5 mg manganese acetate (C4H6MnO4·H2O) and 16.9 mg silver nitrate (AgNO3) were added, and stirring was continued at room temperature for 1.5 h;

[0094] (2) washing the product obtained in step 2) (1) with ultrapure water three times;

[0095] (3) washing the product obtained in step 2) with anhydrous ethanol once;

[0096] (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight;

[0097] (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 600° C. for 2 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction;

[0098] (6) 20 mg of the product obtained in step 2) (5) was ultrasonically dispersed in a mixed solution of 56 mL of anhydrous ethanol and ultrapure water, wherein the volume ratio (V / V) of anhydrous ethanol and ultrapure water was 25:3, and then 160 mg of nickel nitrate (Ni(NO3)2·6H2O) was added, and the mixture was ultrasonically dispersed for 2 h and then reacted in a 120°C forced air drying oven for 4 h;

[0099] (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times;

[0100] (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets.

[0101] See also Figure 1 and Figure 2 As shown, the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The C / N-NiCoMn-LDH / Ag composite electrode material has a novel hollow cage structure as a whole, in which a part of the nanostructure retains the core-shell structure characteristics of the intermediate product; the secondary structure of the composite material is a nanosheet structure, and its staggered arrangement forms abundant pores. The unique structural characteristics of the material expose more active sites to fully interact with electrolyte ions during the charge and discharge process, thereby greatly improving its double layer and pseudocapacitor energy storage characteristics.

[0102] See also Figure 3As shown, X-ray energy spectrum analysis (EDS) was performed on the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention. The composite material is composed of seven elements, Ni, Co, Mn, Ag, C, O, and N, and each element is evenly distributed in the material, which can ensure a stable charge storage and release process.

[0103] See also Figure 4 As shown, the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention was subjected to X-ray diffraction analysis (XRD). The characteristic peaks of the composite material are consistent with the diffraction peaks of the (003), (006), (101), (012), (110) and (112) crystal planes of the typical LDH, but its crystallinity is relatively low, which is mainly due to the large radius of the introduced silver atoms, resulting in deformation of the unit cell structure, thereby evolving into an amorphous structure; in addition, it can be clearly seen from the XRD spectrum of the composite material that it has the characteristic peaks of elemental silver (PDF#87-0597), so it can be judged that the composite material contains NiCoMn-LDH and Ag elemental substances.

[0104] See also Figure 5 As shown, the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention was characterized by X-ray photoelectron spectroscopy (XPS). Analysis shows that the material is mainly composed of Ni, Co, Mn, Ag, C, O, and N elements, among which Ni and Co are mainly +2 and +3 valences, Mn is +3 valence, and Ag exists in the form of elemental silver.

[0105] See also Figure 6 As shown, the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention was subjected to a cyclic voltammetry test (CV) at a scan rate of 5 to 50 mV·s -1 The CV curve obtained from the test has obvious redox peaks, indicating that the material is a typical battery-type energy storage material; in addition, as the scan rate increases, the shape of the CV curve remains basically unchanged, indicating that the material has high reversibility during the energy storage process.

[0106] See also Figure 7 As shown, the C / N-NiCoMn-LDH / Ag composite electrode material prepared in Example 2 of the present invention was subjected to a constant current charge and discharge test (GCD), and the test current density was 1 to 20 A·g -1 Calculated based on GCD discharge time, at 1, 2, 3, 5, 8, 10, 15 and 20 A·g -1 At the current density, the specific capacitance of the composite materials is 1988, 1807, 1702, 1571, 1415, 1319, 1148 and 1023 F·g, respectively. -1The test results show that the electrode material prepared by the present invention has excellent charge storage capacity, and its specific capacitance can still be maintained at 1000F·g under high current density. -1 above.

[0107] In summary, the present invention successfully designed and prepared a C / N-NiCoMn-LDH / Ag composite electrode material with adjustable composition microstructure and crystal structure, determined the key parameters affecting the controllable preparation of the material, and proposed a scientific, reasonable, simple and controllable preparation method; the raw materials used in the preparation are all commercially available products, which are easy to obtain; the prepared C / N-NiCoMn-LDH / Ag composite electrode material has excellent electrochemical properties and has great application prospects in the field of supercapacitors. The results of the present invention are of reference significance for the controllable preparation and performance regulation of composite electrode materials with high electrochemical energy storage performance.

[0108] The embodiments of the present invention are only used to further illustrate the present invention and are not exhaustive and do not constitute a limitation on the protection scope of the claims. Based on the inspiration obtained from the embodiments of the present invention, those skilled in the art can think of other substantially equivalent alternatives without creative work, and all of them are within the protection scope of the present invention.

Claims

1. A method for preparing a C / N-NiCoMn-LDH / Ag composite electrode material, characterized in that: It includes the following steps: 1) Preparation of ZIF-67 precursor (1) preparing 0.04 mol / L cobalt nitrate Co(NO3)2·6H2O and 0.16 mol / L 2-methylimidazole methanol solution respectively, then mixing the two solutions in equal volumes, stirring for 1 to 30 minutes, and aging the mixed solution at room temperature for 20 to 28 hours; (2) washing the product obtained in step 1) (1) with anhydrous ethanol three times; (3) placing the product washed in step (2) of step 1) in a forced air drying oven and drying at 50° C. to constant weight to obtain a ZIF-67 precursor; 2) Preparation of C / N-NiCoMn-LDH / Ag composite electrode materials (1) Take 1 portion of the ZIF-67 precursor obtained in step 1) and ultrasonically disperse it in a tris buffer solution with a pH of 8.5, wherein the solvent of the buffer solution is a mixture of anhydrous ethanol and ultrapure water, and the volume ratio of anhydrous ethanol to ultrapure water is 1:9-49. The concentration of the obtained ZIF-67 dispersion is 0.5 g / L-1 g / L, and then add 1 / 4-2 portions of dopamine hydrochloride C8H 12 ClNO2, magnetically stir for 0.5h, then add 1 / 8 to 1 part of manganese acetate C4H6MnO4·H2O and 1 / 10 to 3 / 10 part of silver nitrate AgNO3, and continue stirring at room temperature for 0.5 to 2.5h; (2) washing the product obtained in step 2) (1) with ultrapure water three times; (3) washing the product obtained in step 2) with anhydrous ethanol once; (4) placing the product washed in step (3) of step 2) in a forced air drying oven and drying at 60° C. to constant weight; (5) placing the product obtained in step 2) (4) in a tube furnace, reacting at 550-700° C. for 1-3 h under a nitrogen atmosphere, with a heating rate set at 2° C. / min, and naturally cooling to room temperature after the reaction is completed; (6) taking 1 part of the product obtained in step 2) (5) and ultrasonically dispersing it in a mixed solution of anhydrous ethanol and ultrapure water, wherein the volume ratio of anhydrous ethanol to ultrapure water is 25:1-9, and the obtained dispersion concentration is 0.04 g / L-0.3 g / L, and then adding 4-10 parts of nickel nitrate Ni(NO3)2·6H2O, continuing ultrasonication for 2 hours, and then reacting in a 110-130°C forced air drying oven for 2-6 hours; (7) washing the product obtained in step 2) (6) with anhydrous ethanol three times; (8) The product washed in step (7) of step 2) is placed in a vacuum drying oven at 60° C. and dried to constant weight to obtain a C / N-NiCoMn-LDH / Ag composite electrode material with a hollow cage structure assembled by nanosheets. By introducing Mn and Ag elements, its crystallinity and surface active sites are effectively regulated, and the material has both high electrochemical reaction activity and high stability.

2. The C / N-NiCoMn-LDH / Ag electrode material obtained by the preparation method of a C / N-NiCoMn-LDH / Ag composite electrode material according to claim 1, wherein the electrode material is a hollow cage structure assembled by nanosheets and a low crystallinity composite electrode material.

Citation Information

Patent Citations

  • C / N-NiCoFeMn LDH composite electrode material and preparation method thereof

    CN114758898A